2007
DOI: 10.1016/j.bbrc.2007.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Protection from ataxia-linked apoptosis by gap junction inhibitors

Abstract: Mutations in the protein kinase C γ (PKCγ) gene cause spinocerebellar ataxia type 14 (SCA14), a heterogeneous neurodegenerative disorder. Synthetic peptides (C1B1) serve as gap junction inhibitors through activation of PKCγ control of gap junctions. We investigated the neuroprotective potential of these peptides against SCA14 mutation-induced cell death using neuronal HT22 cells. The C1B1 synthetic peptides completely restored PKCγ enzyme activity and subsequent control of gap junctions. PKCγ SCA14 mutant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…According to our in vitro cell culture study, PKCγ H101Y mutant cells have milder cell apoptosis phenotype while S119P and G128D mutants are more severe [4, 6]. Therefore, we expected that PKCγ H101Y mutation would not be lethal to the transgenic mutant mouse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our in vitro cell culture study, PKCγ H101Y mutant cells have milder cell apoptosis phenotype while S119P and G128D mutants are more severe [4, 6]. Therefore, we expected that PKCγ H101Y mutation would not be lethal to the transgenic mutant mouse.…”
Section: Resultsmentioning
confidence: 99%
“…In our lab, we have previously used well-characterized, hippocampal neuronal HT22 cells [6,29]. We have demonstrated that these mutant PKCγ’s cause a caspase-3 linked apoptosis in culture and PKCγ SCA14 mutants are not activated by an oxidative signal such as H 2 O 2 when expressed in neuronal HT22 cells in culture [6]. Endogenous wild type PKCγ is negatively affected by the presence of the mutations (ie., a dominant effect).…”
Section: Introductionmentioning
confidence: 99%
“…Retinal ischemia induces retinal cell death in a caspase-dependent manner [13]. We have previously found that inhibition of gap junctions, in hippocampal HT22 cells, prevents oxidative cell death due to H 2 O 2 through a caspase-3 pathway [14]. It is apparent that proper control of gap junctions is essential for neural cell survival [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the established neuronal cell lines, HT22 is one of the widely used hippocampal neuronal cell lines used in a variety of studies (Aminova et al, 2005;Caldwell et al, 2007;Davis and Maher, 1994;Li et al, 1997Li et al, , 1998Lin and Takemoto, 2007;Luo and DeFranco, 2006;Panee et al, 2007;Suo et al, 2003). Given that its parent line, HT4, was known to be capable of mimicking LTP, a critical outcome for memory related studies (Morimoto and Koshland, 1990), we went further to test if HT22 cells possess functional cholinergic neuronal properties.…”
Section: Discussionmentioning
confidence: 98%
“…When grown as a single population of neurons without establishing synaptic connections, the HT4 hippocampal neurons are capable of mimicking short-and longterm potentiation (LTP) and have therefore been proposed as a good model for memory-related studies (Morimoto and Koshland, 1990). Though the HT22 cells, a sub-line cloned from their parent HT4 cells, have been more widely used (Aminova et al, 2005;Caldwell et al, 2007;Davis and Maher, 1994;Li et al, 1997Li et al, , 1998Lin and Takemoto, 2007;Luo and DeFranco, 2006;Panee et al, 2007;Suo et al, 2003), it is still undetermined whether HT22 cells exhibit any cholinergic neuronal characteristics. This study was undertaken to determine if the HT22 cells express any cholinergic markers, and if so, whether they are functional.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 98%